2022
DOI: 10.3390/nu14112320
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast Consumption May Improve Fasting Insulin, HOMA-IR, and HbA1c Levels in Predominately Low-Income, Hispanic Children 7–12 Years of Age

Abstract: Children from low-income households and minority families have high cardiometabolic risk. Although breakfast consumption is known to improve cardiometabolic health in children, limited randomized control trials (RCT) have explored this association in low-income and racial/ethnic U.S. minority families. This study conducted secondary analyses from TX Sprouts, a school-based gardening, cooking, and nutrition education RCT, to examine the intervention effect on breakfast consumption and how changes in breakfast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…In the potential sequence caused by skipping breakfast, glucose homeostasis may occur before energy balance ( 29 , 79 ). Glucose status was improved if breakfast was added among those who habitually skip breakfast, including FBG and HOMA-IR ( 80 , 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the potential sequence caused by skipping breakfast, glucose homeostasis may occur before energy balance ( 29 , 79 ). Glucose status was improved if breakfast was added among those who habitually skip breakfast, including FBG and HOMA-IR ( 80 , 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a randomised cross-over study demonstrated that postprandial metabolic processes have shown higher energy expenditure (resting metabolic rate) in the morning compared with the evening (35) . Research has also suggested protective factors against overweight of earlier, rather than later, food intake throughout the day (8,17) , with more recent evidence highlighting improved glycaemic control with increased breakfast consumption in children (36) . Consuming a larger breakfast may suppress appetite and improve satiety and diet quality (10) .…”
Section: Discussionmentioning
confidence: 99%
“…This is a critical community from the perspective of those interested in increasing the health of the whole population because communities that focus on promoting healthy foods and healthy lifestyles have a high potential to improve the nutritional composition of the foods consumed by the population exposed to these messages (Love et al, 2018). Overall, it has been shown (Jean et al, 2019) that social media influencers play a crucial role in stimulating positive attitudes among consumers, which can subsequently impact their purchase intentions.…”
Section: Topic Analysismentioning
confidence: 99%
“…The goal of interest groups is a healthy society. In the context of research showing that daily breakfast consumption is associated with maintaining a healthy body weight (Dubois et al, 2009), reduces stress and depression in adolescents (Ferrer-Cascales et al, 2018), improves carbohydrate metabolism and insulin levels (Maki et al, 2016;Jeans et al, 2022), and positively correlates with cognitive and emotional engagement (Moller et al, 2022), consumption of a high-quality breakfast plays a critical role in promoting both mental and physical health.…”
Section: Topic Analysismentioning
confidence: 99%